Forward Chaining Method in Expert System for Diagnosing Pests and Plant Diseases: A Systematic Literature Review - Goda, Karina Dhena; Bay, Jenny Ronawati (Yayasan Kita Menulis, 2024)
Pest and disease attacks on plants are very detrimental factors for farmers. Lack of knowledge leads to a difficult diagnosis of attacks and slow control. The technology that can help farmers in diagnosing plant pests and diseases is the expert system. One of the most widely used algorithms is forward chaining. Although there have been many used further research is needed to determine the effectiveness of this method. This research wants to find out more advantages, types of platforms used, and benefits of expert systems with forward chaining algorithms. This study uses a systematic method literature review (SLR) to collect, assess, and analyze data systematically from various scientific articles. The results of the study show that the use of forward chaining has advantages and benefits for developers and farmers.